No summit out of sight : the true story of the youngest person to climb the seven summits - Romero, Jordan, 1996- (Simon & Schuster BFYR, 2015)
"The story of Jordan Romero, who at the age of 13 became the youngest person ever to reach the summit of Mount Everest. At age 15, he reached the summits of the world's 7 highest mountains"--Provided by publisher.